Pembahasan Mengenai Asas-Asas Dalam Ranah Hukum Militer Dan Hukum Pidana Umum - Astri Dewi Setyarini; Muhammad Rafli; Sefriyan Reynaldi; Fajar Muhammad; Samuel Arthur Hulu (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
The influence of general criminal law principles and military law principles on actions and law enforcement in each field. The discussion includes an in-depth analysis of the principle of legality in general criminal law, emphasizing the need for a clear legal basis in upholding justice. Meanwhile, the principle of discipline in military law becomes a separate focus in assessing law enforcement in the military environment and its impact on order. Conflict or harmony between these two principles, especially in the context of courts and law enforcement. Thus, this journal seeks to provide a deeper understanding of the role of these two principles in the context of general criminal law and military law and their implications for law enforcement in Indonesia.